Evaluation of Chronic Kidney Disease Risk Factors after Radical Nephrectomy - Jurijus Makevičius; Akvilė Pajaurytė; Artūras Samuilis; Raminta Lukšaitė-Lukštė; Eugenijus Jasiūnas; Feliksas Jankevičius; Marius Miglinas (Applied Sciences, 2023)
Intraoperative hypotension (IOH) and loss of blood during radical nephrectomy (RN) cause postoperative clinically significant renal dysfunction, which after 12 months can cause a reduction in serum creatinine clearance of <60 mL/min. We conducted a prospective study of 93 adult patients in which we investigated the risk factors for developing chronic kidney disease (CKD) after RN. Forty-six (49.5%) patients had CKD, and of them, 43 patients had acute kidney injury (AKI) 48 h after surgery. Sixty-six (73.1%) of the postoperative AKI patients had CKD upstage. With each 1 mL estimated blood loss during RN (OR 1.01, p < 0.001), IOH was evaluated as the main risk factor of postoperative CKD development (OR 1.09, p < 0.01). Dunn’s t-test revealed that only clinically significant AKI had a main effect (g = −1.08, p < 0.0001) on renal function 1 year after RN. A higher preoperative estimated glomerular filtration rate (eGFR), OR 0.89, p = 0.02, and contralateral kidney CT volume (OR 0.97, p = 0.04) had a clinically significantly decreased risk of postoperative CKD. Risk factors of AKI with CKD upstage were a small contralateral kidney CT volume (OR 46.70), NLR > 3.5 (OR 1.42), higher primary eGFR (OR 1.13) and longer IOH (OR 1.05), and for all of these, p < 0.03. A half of all patients after RN are at increased risk of CKD. Longer IOH and increased blood loss during RN are significant risk factors for CKD. Clinically significant postoperative AKI is related with a developed risk for postoperative eGFR decline and the presence of CKD 12 months after RN, and can be predicted by NLR > 3.5. A higher preoperative eGFR and contralateral kidney CT volume reduces the risk of postoperative CKD.